Ongoing Computed Tomography Appraisal of Intestinal Perforation Due to an Ingested Foreign Body - Cicero, Giuseppe (Am J Case Rep, 2019)
Patient: Female, 73 Final Diagnosis: Ileal perforation due to the ingestion of a foreign body Symptoms: Abdominal discomfort • nausea • vomiting Medication: — Clinical Procedure: CT-scan Specialty: Radiology OBJECTIVE: Unusual clinical course BACKGROUND: Diagnosis and management of accidental or intentional ingestion of foreign bodies is a common problem at in emergency departments. This condition is generally observed in patients with limited consciousness or attention, such as children, elders, or psychiatric patients. Here, we report a case of intestinal perforation caused by ingestion of a foreign body that occurred during the performance of a contrast-enhanced CT scan. CASE REPORT: A 73-year-old diabetic woman was admitted to the emergency room of our hospital with postprandial abdominal discomfort, nausea, and vomiting. Under the suspicion of bowel ischemia, the patient underwent a contrast-enhanced CT scan. A thickened ileal loop with an endoluminal bone-density foreign body was detected. The following contrast-enhanced acquisitions additionally showed air bubbles adjacent to the loop, as the sign of an intestinal perforation that occurred between the basal and the contrast-enhanced acquisitions. CONCLUSIONS: Caution should be always exercised in patients with suspected gastrointestinal perforation, especially if caused by ingested foreign bodies. A high degree of suspicion and a CT scan may prevent delays in the diagnosis and clinical management of these patients.